Biomarkers in advanced larynx cancer. (12th July 2013) - Bradford, Carol R.; Kumar, Bhavna; Bellile, Emily; Lee, Julia; Taylor, Jeremy; D'Silva, Nisha; Cordell, Kitrina; Kleer, Celina; Kupfer, Robbi; Kumar, Pawan; Urba, Susan; Worden, Francis; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine if tumor biomarkers were predictive of outcome in a prospective cohort of patients with advanced larynx cancer treated in a phase II clinical trial. Study Design Prospectively collected biopsy specimens from 58 patients entered into a Phase II trial of organ preservation in advanced laryngeal cancer were evaluated for expression of a large panel of biomarkers, and correlations with outcome were determined. Methods Tissue microarrays were constructed from pretreatment biopsies and stained for cyclin D1, CD24, EGFR, MDM2, PCNA, p53, survivin, Bcl‐xL, Bcl‐2, BAK, rhoC, and NFκB. Pattern of invasion and p53 mutations were assessed. Correlations with overall survival (OS), disease‐specific survival (DSS), time free from indication of surgery, induction chemotherapy response, and chemoradiation response were determined. Cox models were used to assess combinations of these biomarkers. Results Low expression of BAK was associated with response to induction chemotherapy. Low expression of BAK and cytoplasmic NFκB was associated with chemoradiation response. Aggressive histologic growth pattern was associated with response induction chemotherapy. Expression of cyclin D1 was predictive of overall and disease‐specific survival. Overexpression of EGFR was also associated with an increased risk of death from disease. Bcl‐xL expression increased significantly in persistent/recurrent tumors specimens when compared to pretreatment specimens derived from the same patient (P = 0.0003). Conclusions Evaluation of biomarker expression in pretreatment biopsy specimens can lend important predictive and prognostic information for patients with advanced larynx cancer. Level of Evidence N/A. Laryngoscope, 124:179–187, 2014